On biodiversity and conservation of the Iris hexagona complex (Phaeiris, Iridaceae). Issue 1 (26th January 2021) - Mavrodiev, Evgeny V.; Gómez, Juan P.; Mavrodiev, Nicholas E.; Melton, Anthony E.; Martínez‐Azorín, Mario; Crespo, Manuel B.; Robinson, Scott K.; Steadman, David W.
Abstract: Taxonomic revisions using newly available molecular data can have profound consequences for identifying areas of high endemism and, therefore, high conservation priority. A good example of the connection between taxonomy, biodiversity ecology, and conservation issues is genus Phaeiris ( Iris subsect. Hexagonae ), an endemic taxon of the southeastern United States and in particular P. hexagona ( I. hexagona ) (Blue Flag), perhaps the best‐known species of this genus. Some authors recently provided evidence for the need to revise the taxonomy of the Blue Flag, which has usually been considered to consist of a single species, P. hexagona . Using molecular and bioclimatic analyses of Blue Flags from Florida and Louisiana, collected at their loci classici, we challenge the notion that P. hexagona is a single species, referring to the almost forgotten taxonomic context of Phaeiris as established by John K. Small and Edward J. Alexander nearly 90 yr ago. Our vision of the P. hexagona complex reinforces the current treatment of Southern Coastal Plain as a biodiversity hotspot. Our results also argue for the complex nature of endemism on the Florida Peninsula, and elsewhere on the Southern Coastal Plain, including a new interpretation of the well‐studied Louisiana irises. We also propose that the valleys of Florida rivers and lakes are likely to harbor additional hidden biodiversity. Accurate taxonomy proved to be a heuristic tool to characterize better the actual level of biodiversity within Southern Coastal Plain as well as to describe the different areas endemism. The newly re‐documented taxonomic diversity in broadly defined P. hexagona should also be considered in future conservation efforts.